2023
DOI: 10.1021/acs.analchem.3c01638
|View full text |Cite
|
Sign up to set email alerts
|

Diamonds in the Rough: Direct Surface Enhanced Infrared Spectroscopic Evidence of Nitrogen Reduction on Boron-Doped Diamond Supported Metal Catalysts

Abstract: In situ investigations of electrocatalytic processes of increasing societal interest such as the nitrogen reduction reaction (NRR) require aggressive experimental conditions that are not readily compatible with surface sensitive techniques such as attenuated total reflection surface enhanced infrared absorption spectroscopy (ATR-SEIRAS). A method for performing ATR-SEIRAS studies at very negative potentials where conventional IR-active films delaminate and fail is reported. The method relies on a thin film of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Figure b shows the results of the analogous, potential-dependent experiment, using an iAu@ITO modified Si IRE. In a previous study, ,, the iAu@ITO system provided strong SEIRAS signals for species directly adsorbed on the Au islands from dilute solutions as verified in the Supporting Information. Thus, it was expected that the iAu@ITO system would provide much greater IR sensitivity to the innermost layer of ions adsorbed to the gold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure b shows the results of the analogous, potential-dependent experiment, using an iAu@ITO modified Si IRE. In a previous study, ,, the iAu@ITO system provided strong SEIRAS signals for species directly adsorbed on the Au islands from dilute solutions as verified in the Supporting Information. Thus, it was expected that the iAu@ITO system would provide much greater IR sensitivity to the innermost layer of ions adsorbed to the gold.…”
Section: Resultsmentioning
confidence: 99%
“…Although gold adheres very strongly to ITO, conductive metal oxides are susceptible to electrochemical degradation at large negative potentials. It was recently demonstrated that replacing ITO with a thin film of boron-doped diamond (BDD) allows ATR–SEIRAS measurements to be performed in very aggressive electrochemical conditions . An ATR–SEIRAS layer of iAu/cAu on a thin film of BDD deposited on a Si IRE was prepared to investigate the metal/IL interface with ATR–SEIRAS at potentials well removed from the pzc.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the chemical susceptibilities of the most commonly used TCOs, which include indium tin oxide (ITO), indium zinc oxide (IZO), and fluorine-doped tin oxide (FTO), this can severely limit the accessible range of surface potentials and pH values during in situ electrochemical FTIR experiments. To overcome these stability limitations, an alternative method based on boron-doped diamond (BDD) thin films to replace the TCO layer was recently reported and shows exceptional stability over a broad range of electrochemical potentials . While such BDD layers offer great promise for in situ studies, they also require specialized chemical vapor deposition reactors for fabricating the coatings and are characterized by spectral absorption in the 1100–1300 cm –1 range, which could interfere with some measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these stability limitations, an alternative method based on boron-doped diamond (BDD) thin films to replace the TCO layer was recently reported and shows exceptional stability over a broad range of electrochemical potentials. 30 While such BDD layers offer great promise for in situ studies, they also require specialized chemical vapor deposition reactors for fabricating the coatings and are characterized by spectral absorption in the 1100–1300 cm –1 range, which could interfere with some measurements. Furthermore, the comparatively high resistivities of the diamond layers and TCOs lead to long RC time constants that limit the temporal resolution of such electrodes for time-resolved in situ electrochemical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Preparing a chemically stable barrier layer on a Si window is a plausible way to address the above challenges. Although conductive indium zinc oxide (IZO) and indium tin oxide (ITO) prepared by magnetron sputtering were reported as an adhesion layer between an electrodeposited metal film and Si substrate for in situ ATR-SEIRAS in neutral electrolytes, they were not targeted for strong alkaline media. Until recently, Burgess et al reported Ni thin films on ITO-modified Si IRE to probe the methanol oxidation reaction in 1 M KOH .…”
mentioning
confidence: 99%